The Association of High Body Mass Index with the Risk of Placenta Previa: A Systematic Review - Ivandra Septiadi Tama Putra; Penri Fransiskus Manulang; Jansen Renaldi; Lidya Aprilia Sari (The Indonesian Journal of General Medicine, 2025)
Introduction: Placenta previa is a significant cause of maternal and neonatal morbidity, primarily due to antepartum hemorrhage. Concurrently, the global prevalence of maternal obesity is rising, a condition associated with numerous adverse pregnancy outcomes. The direct relationship between high maternal Body Mass Index (BMI) and the risk of developing placenta previa remains contentious, with conflicting evidence from observational studies. This systematic review aims to critically appraise and synthesize the available evidence to clarify this association. Methods: A systematic search of PubMed, Google Scholar, Semanthic Scholar, Springer, Wiley Online Library was conducted to identify all relevant cohort and case-control studies published in English. Studies were included if they investigated the association between pre-pregnancy or early-pregnancy BMI (categorized as overweight or obese) and the incidence of placenta previa in pregnant women, compared to those with a normal BMI. Two independent reviewers performed study selection, data extraction, and quality assessment using the Newcastle-Ottawa Scale (NOS). A formal risk of bias assessment was also conducted using the Cochrane Risk of Bias in Non-randomized Studies - of Interventions (ROBINS-I) tool. A narrative synthesis of the findings was performed. Results: Seventeen studies, comprising large-scale retrospective cohorts and case-control studies, met the inclusion criteria. The majority of high-quality studies, particularly those with robust adjustment for confounding variables, found no statistically significant direct association between high maternal BMI and the risk of placenta previa. Unadjusted analyses in some studies suggested a weak association, but this effect was consistently attenuated and lost statistical significance after controlling for key confounders, most notably a history of prior cesarean delivery. Analysis of secondary outcomes revealed that high BMI is strongly associated with an increased risk for primary cesarean delivery, gestational diabetes, and preeclampsia. Discussion: The weight of the evidence suggests that high maternal BMI is not an independent, direct risk factor for placenta previa. The association observed in unadjusted analyses is likely an artifact of confounding. A plausible indirect causal pathway is proposed: high BMI increases the risk of a primary cesarean delivery in a woman's first pregnancy, and the resultant uterine scarring is a powerful, established risk factor for placenta previa in a subsequent pregnancy. The pathophysiological mechanisms of obesity, such as systemic inflammation, appear to drive metabolic and hypertensive complications rather than influencing the specific site of placental implantation. Conclusion: The link between high maternal BMI and placenta previa is indirect, mediated primarily through the increased rate of cesarean delivery. Clinical counseling for women with high BMI should emphasize the well-established risks of gestational diabetes, hypertensive disorders, and the increased likelihood of a primary cesarean section, along with the long-term reproductive consequences of that surgery, including a future risk of placenta previa.